Efficient fullerene-based and fullerene-free polymer solar cells using two wide band gap thiophene-thiazolothiazole-based photovoltaic materials. Issue 24 (1st June 2016) - Zhao, Kang; Wang, Qi; Xu, Bowei; Zhao, Wenchao; Liu, Xiaoyu; Yang, Bei; Sun, Mingliang; Hou, Jianhui
Abstract : Efficient fullerene-based and fullerene-free PSCs were fabricated based on two wide band gap polymers PBT-TTz and PBT-S-TTz. Abstract : Two wide band gap (WBG) polymers based on thiophene-thiazolothiazole (TTz) units, PBT-TTz and PBT-S-TTz, were synthesized. Both polymers showed absorption onsets at 635 nm in solid films. Although PBT-TTz and PBT-S-TTz are WBG materials with relatively narrow absorption spectra, they have great potential for constructing high-performance polymer solar cells (PSCs). By replacing the alkyl side chain of PBT-TTz with an alkylthiol side chain, the HOMO level of PBT-S-TTz was lowered to −5.45 eV. A PCE of 7.92% was then obtained in a single-junction PSC device based on a PBT-S-TTz:PC71 BM active layer. Moreover, high-performance fullerene-free PSCs were fabricated using these polymers and a high PCE of 8.22% was achieved. This work demonstrates that TTz-based polymers PBT-TTz and PBT-S-TTz are promising candidates as efficient WBG polymers for constructing high-performance PSC devices.